Analisis Penerapan Internal Audit Capability Model (IA-CM) Pada Inspektorat Kota Bukittinggi - Deri Oktaveni; Perengki Susanto (CV. ITTC INDONESIA, 2025)
This study analyzes the implementation of the Internal Audit Capability Model (IA-CM) at the Inspectorate of Bukittinggi City to strengthen the capability of the Government Internal Supervisory Apparatus (APIP). The research problem arises from the gap between the formal achievement of APIP capability at Level 3 (Integrated) and the increasing number of internal control system (SPI) weaknesses identified by external auditors, along with the declining performance indicators of regional oversight. This condition indicates that administrative achievements do not fully reflect the substantive effectiveness of oversight functions in preventing and mitigating risks of irregularities. The study employed a qualitative case study approach, with data collected through in-depth interviews with seven key informants, document analysis, and participatory observation. Data were analyzed using the thematic analysis method of Braun and Clarke (2006) supported by NVivo software. The findings reveal that APIP capability has reached Level 3 (Integrated) based on self-assessment and evaluation by BPKP, yet challenges remain in human resource management, internal communication systems, and the strategic role of APIP in consultation and governance. Although formal structures are already in place, their implementation has not fully supported the value-adding and consultative functions of APIP. This study reinforces the relevance of IA-CM as a framework for internal audit development in the public sector and highlights the importance of integrating institutional theory and dynamic capabilities theory to understand the challenges of strengthening internal oversight functions.